Portugal’s position on resettlement: a view from the periphery of the EU - Sousa, Lúcio (2017)
The evolution of European policy in recent years has shown how policy can be used to actively restrict the movement of people and as a mechanism for choosing what kind of refugee a particular country receives, with the interests of states prevailing over humanitarian needs.